2021
DOI: 10.1016/j.marchem.2021.104000
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of iodide to iodate by cultures of marine ammonia-oxidising bacteria

Abstract: Reaction with iodide (I -) at the sea surface is an important sink for atmospheric ozone, and causes sea-air emission of reactive iodine which in turn drives further ozone destruction. To incorporate this process into chemical transport models, improved understanding of the factors controlling marine iodine speciation, and especially sea-surface iodide concentrations, is needed. The oxidation of Ito iodate (IO3 -) is the main sink for oceanic I -, but the mechanism for this remains unknown. We demonstrate for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
4
7
1
Order By: Relevance
“…In our time-series data (Figure 9 and Supplementary Material Figure S2), nitrification is correlated with the reduction of iodate rather the oxidation of iodide, which appears to contradict the finding from studies with microbial cultures that ammonia oxidation is a sink for iodide (Hughes et al, 2021). However, despite the correlation, our results should not be taken to imply that nitrification is responsible for the increase of iodide.…”
Section: Fate Of Subsurface Iodidecontrasting
confidence: 99%
See 1 more Smart Citation
“…In our time-series data (Figure 9 and Supplementary Material Figure S2), nitrification is correlated with the reduction of iodate rather the oxidation of iodide, which appears to contradict the finding from studies with microbial cultures that ammonia oxidation is a sink for iodide (Hughes et al, 2021). However, despite the correlation, our results should not be taken to imply that nitrification is responsible for the increase of iodide.…”
Section: Fate Of Subsurface Iodidecontrasting
confidence: 99%
“…One suggestion is that the oxidation of iodide is connected with ammonium oxidation during nitrification. Hughes et al (2021) demonstrated that ammonium oxidising bacteria can mediate iodide oxidation to iodate during culture incubations with added excess iodide. Wadley et al (2020) built this process into their global model of iodine cycling where surface layer nitrification played a key role as a "fast" sink for iodide, especially in sub-tropical waters.…”
Section: Fate Of Subsurface Iodidementioning
confidence: 99%
“…(2020) found the best fit to the measured distributions when it was assumed that iodide oxidation was correlated with the first step in nitrification: ammonia oxidation. This is consistent with recent data showing that some ammonia oxidizing bacteria can oxidize iodide, while others possess multicopper oxidases (similar to ammonium monooxygenase) that oxidize iodide (Hughes et al., 2021; Long et al., 2015; Truesdale et al., 2001; Yeager et al., 2017). Ammonia oxidation is inhibited at high light intensities and is slow in permanently stratified tropical waters (Horak et al., 2018), so iodide oxidation may also be light inhibited as well.…”
Section: Discussionsupporting
confidence: 90%
“…As total iodine in surface ocean waters is lower by a few percent compared to deep waters (Wong, 1991), the decomposition of organic-iodine leads to some Irelease, which may be oxidized to IO − 3 by ammonia-oxidizing bacteria (Hughes et al, 2021). This is similar to release and oxidation of NH + 4 to NO − 3 from particulate organic matter in deep waters that results in an increase of NO − 3 concentration with depth (recycled element profile).…”
Section: Hoi and I 2 Formation Leads To Organic Iodinementioning
confidence: 99%
“…Thus, other oxidants are required to initiate abiotic iodide oxidation, and Iis a known sink for O 3 . Biotic iodide oxidation has received much interest with one report showing conversion of iodide to iodate (Hughes et al, 2021). Iodate reduction can occur with common reductants (e.g., sulfide, Fe 2+ ), and various organisms that decompose organic matter using iodate as the electron acceptor.…”
Section: Introductionmentioning
confidence: 99%